The Missed symptoms of behjet’s disease - Altaha, lama H. (Journal of the Faculty of Medicine Baghdad, 2021)
Abstract Objectives: Behçet’s disease is a systemic chronic proinflammatory vascular disease .this study wants to describe more details of patients with Behçet’s disease in iraq. Methods: Any patient with suspected or diagnosed Behçet’s disease attending centre of dermatology/behjet unit , 2017- 2018. A total 47 patients ,Full history and examination were taken. Percentage of complains were calculated. Results: 37 were females and 10 were males , Age of patients ranged from (11-63) years.Pethargy test was negative in 13 patients , positive in 15 ,21 had negative family history and 9 had positive . They complain from Malaise , oral ulcer, genital ulcer, unexplained fever ,20 symptoms began from childhood ,decreased hearing,eye complain, dysphagia , dyspnea ,headache , memory problems, depression , muscle contraction, peripheral paresthesia , joint complains, sleep disturbances and renal problems. Conclusion: describes new symptoms can help in diagnosis of behjet’s disease .